Examining Islamic Funds Underperformance: The Case Of Malaysia - Mohd Rahimie Abd Karim (Universiti Sains Islam Malaysia, 2015)
Despite operating in a niche market, Islamic funds continue to face considerable challenge from conventional funds. Past studies have shown that the return of Islamic funds is generally lower whilst their risk is higher as compared to conventional funds and market index. This study attempts to investigate the reasons for the Islamic funds’ underperformance in Malaysia. The study found that the poor performance relative to conventional funds and benchmark index is arguably caused by the inability of Islamic funds to achieve optimal diversification. The major contributing factor is the Shariah-compliance restrictions, a feature unique to Islamic funds, which limit the Islamic funds access to those more stable and profitable industries and largecapitalised stocks.